Investigating the early stages of mineral precipitation by potentiometric titration and analytical ultracentrifugation - Kellermeier, M.; Cölfen, H.; Gebauer, Denis (Academic Press, 2013)
Despite the importance of crystallization for various areas of research, our understanding of the early stages of the mineral precipitation from solution and of the actual mechanism of nucleation is still rather limited. Indeed, detailed insights into the processes underlying nucleation may enable a systematic development of novel strategies for controlling mineralization, which is highly relevant for fields ranging from materials chemistry to medicine. In this work, we describe experimental aspects of a quantitative assay, which relies on pH titrations combined with in situ metal ion potentiometry and conductivity measurements. The assay has originally been designed to study the crystallization of calcium carbonate, one of the most abundant biominerals. However, the developed procedures can also be readily applied to any compound containing cations for which ion-selective electrodes are available. Besides the possibility to quantitatively assess ion association prior to nucleation and to directly determine thermodynamic solubility products of precipitated phases, the main advantage of the crystallization assay is the unambiguous identification of the different stages of precipitation (i.e., prenucleation, nucleation, and early postnucleation) and the characterization of the multiple effects of additives. Furthermore, the experiments permit targeted access to distinct precursor species and intermediate stages, which thus can be analyzed by additional methods such as cryo-electron microscopy or analytical ultracentrifugation (AUC). Regarding ion association in solution, AUC detects entities significantly larger than simple ion pairs, so-called prenucleation clusters. Sedimentation coefficient values and distributions obtained for the calcium carbonate system are discussed in light of recent insights into the structural nature of prenucleation clusters. © 2013 Elsevier Inc.